INFLUENCE OF GAMMA RADIATION AND PACKAGING MATERIALS ON GERMINATION PARAMETERS IN AROMATIC RICE VARIETY SUGANDHA SAMBA DURING STORAGE - K. KESHAVULU, K. AMBICA SONI, M. SREEDHAR, S. VANISREE and (The Journal of Research, PJTSAU, 2017)
Aromatic rice constitute a small but special group in India considered as the best for eating quality parameters. Majority of the indigenous non-basmati aromatic rice, constitute small and medium grain types, possessing excellent aroma and good cooking qualities with respect to kernel elongation after cooking, softness, mouth feel and taste.A short grain variety Sugandha Samba released in Telangana for commercial cultivation facilitates availability of scented rice at relatively affordable price for an average consumer. Sugandha samba gives 5.5-6.0 t ha-1 of yield along with strong scent owing to the presence of higher percentage of aroma component 2-acetyl-1-pyrroline.